A review of anti-inflammatory, antioxidant, and immunomodulatory effects of Allium cepa and its main constituents. (1st January 2021) - Marefati, Narges; Ghorani, Vahideh; Shakeri, Farzaneh; Boskabady, Marzie; Kianian, Farzaneh; Rezaee, Ramin; Boskabady, Mohammad Hosein
Abstract: Context: Allium cepa L. (Liliaceae), known as onion, is consumed throughout the world. Onion and its derivatives including saponins, aglycones, quercetin, cepaenes, flavonoids, organosulfurs, and phenolic compounds, showed various pharmacological properties and therapeutic effects. Objective: Anti-inflammatory, antioxidant, and immunomodulatory effects of A. cepa and its main constituents, along with the underlying molecular mechanisms are presented. Methods: Databases including, Web of Knowledge, Medline/PubMed, Scopus, and Google Scholar were checked for articles published between 1996 and the end of July 2020, using the key-words Allium cepa, quercetin, anti-inflammatory, antioxidant and immunomodulatory. Results: A. cepa and its constituents mainly quercetin showed anti-inflammatory effects mediated via reduction of total and differential WBC counts, inhibition of chemotaxis of polymorphonuclear leukocytes, COX, and LOX pathways and prevented formation of leukotrienes and thromboxanes, prostaglandin E2 (PGE2) as onVCAM-1, NF-κB, MARK, d STAT-1, JNK, p38 and osteoclastogenesis. A. cepa and its derivatives showed antioxidant effect by decreasing lipid peroxidation, NAD(P)H, MDA, NO, LPO and eNOS but enhancing antioxidants such as SOD, CAT, GSH, GPx, GSPO, TrxR, SDH, GST and GR activities and thiol level. Immunomodulatory effects of the plant and quercetin was also shown by reduction of Th2 cytokines, IL-4, IL-5, and IL-13 as well as IL-6, IL-8, IL-10, IL-1β and TNF-α and IgE levels, but increased CD4 cells, IFN-γ level and IFN-γ/IL4 ratio (Th1/Th2 balance). Conclusions: The effect of onion and its constituents on oxidative stress, inflammatory and immune system were shown indicating their therapeutic value in treatment of various diseases associated with oxidative stress, inflammation, and immune-dysregulation.